2018
DOI: 10.21037/tgh.2018.06.09
|View full text |Cite
|
Sign up to set email alerts
|

Targeting autophagy in liver cancer

Abstract: Autophagy is a catabolic cellular process conserved in animals. It is characterized by the main role of recycling all the non-functional products of the cells. Once, autophagy players detect non-functioning sub-cellular organelles and proteins, they start the so-called nucleation process. The organelles will be surrounded by a double membrane vesicle mainly constituted by endoplasmic reticulum (ER) membrane and autophagy proteins, e.g., MAP1LC3B, Beclin-1, VPS34, Unc-51 like autophagy activating kinase (ULK1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 111 publications
(127 reference statements)
0
19
0
Order By: Relevance
“…Autophagy is a conserved intracellular process and plays an important role in preserving cellular homeostasis by degrading and recycling misfolded proteins and damaged organelles [ 11 ]. Autophagy is strongly induced upon environmental stresses and in most contexts promotes tumorigenesis [ 11 , 33 , 36 , 37 ]. Previous studies by us [ 14 , 33 , 38 ] and other groups [ 39 , 40 , 41 ] have demonstrated that cell autophagy is involved in HCC progression, which results in drug resistance and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a conserved intracellular process and plays an important role in preserving cellular homeostasis by degrading and recycling misfolded proteins and damaged organelles [ 11 ]. Autophagy is strongly induced upon environmental stresses and in most contexts promotes tumorigenesis [ 11 , 33 , 36 , 37 ]. Previous studies by us [ 14 , 33 , 38 ] and other groups [ 39 , 40 , 41 ] have demonstrated that cell autophagy is involved in HCC progression, which results in drug resistance and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The significantly weaker tumor suppressor role of Atg4C needs further research to establish the key function of the autophagy mechanism in tumor suppression. Nonetheless, in hematological tumorigenesis and solid malignancies, particularly liver cancer, autophagy defects are observed [4]. The function of interferon-γ (IFN-γ) with proliferation inhibition on HCC has been shown by Li et al [83].…”
Section: Autophagy-mediated Tumor Suppressionmentioning
confidence: 99%
“…Autophagic aberrations cause oxidative stress, contributing to gene alterations, and could transform the cells to change their metabolism with the development of malignant cells. Autophagy, by contrast, acts as an anticancer mechanism, inhibiting the malignant transformation of normal cells into cancer cells [4]. In comparison, autophagy is also implicated in different stages of cancer development and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…An excessive stimulation of autophagy can be lethal for cancer cells either due to excess elimination of intracellular organelles and cytoplasmic content or activation of the Na + /K + ATPase pump to change membrane osmolality and ion transport 12,14 . Several studies suggested that treatment with some of the inhibitors results in induction of autophagy, leading to cell death of HCC 15,16 . The clinical lysosomotropic autophagy inhibitor chloroquine cooperates with the AKT inhibitor AZD5363 to inhibit autophagy, and sensitizes tumor cells to AZD5363-induced cell death in prostate cancer xenograft models, offering as a potential therapeutic approach in the clinic 17 .…”
Section: Introductionmentioning
confidence: 99%